Validity and reliability of smartphone magnetometer-based goniometer evaluation of shoulder abduction – A pilot study. Issue 6 (December 2015) - Johnson, Linda B.; Sumner, Sean; Duong, Tina; Yan, Posu; Bajcsy, Ruzena; Abresch, R. Ted; de Bie, Evan; Han, Jay J.
Abstract: Background: Goniometers are commonly used by physical therapists to measure range-of-motion (ROM) in the musculoskeletal system. These measurements are used to assist in diagnosis and to help monitor treatment efficacy. With newly emerging technologies, smartphone-based applications are being explored for measuring joint angles and movement. Objective: This pilot study investigates the intra- and inter-rater reliability as well as concurrent validity of a newly-developed smartphone magnetometer-based goniometer (MG) application for measuring passive shoulder abduction in both sitting and supine positions, and compare against the traditional universal goniometer (UG). Design: This is a comparative study with repeated measurement design. Methods: Three physical therapists utilized both the smartphone MG and a traditional UG to measure various angles of passive shoulder abduction in a healthy subject, whose shoulder was positioned in eight different positions with pre-determined degree of abduction while seated or supine. Each therapist was blinded to the measured angles. Concordance correlation coefficients (CCCs), Bland–Altman plotting methods, and Analysis of Variance (ANOVA) were used for statistical analyses. Results: Both traditional UG and smartphone MG were reliable in repeated measures of standardized joint angle positions (average CCC > 0.997) with similar variability in both measurement tools (standard deviation (SD) ± 4°). Agreement between the UG and MG measurements was greater than 0.99 in all positions. Conclusion: Our results show that the smartphone MG has equivalent reliability compared to the traditional UG when measuring passive shoulder abduction ROM. With concordant measures and comparable reliability to the UG, the newly developed MG application shows potential as a useful tool to assess joint angles. Highlights: Built-in magnetometer in smartphone is examined for use in joint angle measurement. Magnetometer-based goniometer demonstrates validity against a standard goniometer. Smartphone magnetometer-based goniometer can measure shoulder abduction reliably. Inter-rater and intra-rater reliability is comparable against the standard universal goniometer. Relative ease-of-use and portability of a smartphone goniometer is promising.